Climate Change and Global Crop Productivity - Reddy, K.R (CABI, 2014)
Human activities are creating changes in our earth ecosystem. Emissions of carbon dioxide and other greenhouse gases are increasing. The evidence, using state-of-the-art computer models incorporating as much of the theoretical understanding of the earth’s weather as possible, suggests that global warming is occurring along with shifting patterns of rainfall and incidences of extreme weather events. The rate of global climate change and warming expected over the next century is more than has occurred during the past 10,000 years. Changes in global environment will have profound effects and consequences for natural and agricultural ecosystems and for society as a whole. These changes could alter the location of the major crop production regions on the earth. Agricultural productivity is particularly vulnerable to disruption by weather. In the coming years, we have to produce more food, fibre and other commodities to cope with increasing population under diminishing per capita arable land and water and degrading soil resources and expanding biotic stresses. In addition to the above stringent constraints, shifting from ‘normal weather’, with its associated extreme events, zones of crop adaptation and cultural practices required for successful crop production will also surely change. Also, plant responses to climatic changes are not uniform and thus there will be winners and losers. Climate and weatherinduced instability in food and fibre supplies will alter social and economic stability and regional competitiveness.